ANALISIS TINGKAT KECELAKAAN LALU LINTAS PADA RUAS JALAN BRAWIJAYA KABUPATEN MERAUKE - Selestinus P. Katabia; Toar Pangkey; Tendly Maki (Sustainable Construction (SUSCON), 2024)
Traffic accidents are a significant issue in transportation activities caused by the movement of vehicles. Three main factors influencing transportation movement are the balance between the driver, the vehicle, and the traffic infrastructure. This research focuses on an area with a high rate of traffic accidents, specifically from Jalan Brawijaya to Jalan Polder Kodim in the Merauke District, Merauke Regency, South Papua Province, covering approximately 3 km. The study uses both primary and secondary data. Primary data were obtained through direct observation to gather actual information before and after improvement efforts were made, including the completeness of road signs and traffic flow conditions on the roads. Secondary data include traffic accident records from 2019 to 2022 obtained from the Traffic Unit (SatLanTas) of Merauke Police and technical data on the condition of Jalan Brawijaya, including its signage system. Surveys on Jalan Brawijaya show that segments 1 and 2 have flexible pavement structures with good compressive strength, making them resistant to damage. Based on the research results, the road conditions are divided into several sections. Segments 1 and 2 have flexible pavement with good compressive strength and reasonably good shoulders. However, segment 3, which connects Jalan Brawijaya to Jalan Trikora, has suffered severe damage due to flooding, causing potholes in the asphalt and damaged shoulders. Additionally, segments 1 and 3 are not yet equipped with traffic signs, making it difficult for drivers.